STRUKTUR KOMUNITAS IKAN DI PERAIRAN DANAU MELINTANG KECAMATAN MUARA WIS KABUPATEN KUTAI KARTANEGARA - Amelia Putri Hendrayani; Moh. Mustakim Mustakim; Paulus Taru (Jurnal Tropical Aquatic Sciences, 2022)
Melintang Lake (Kenohan) is a lake located in the Mahakam river area in Kutai Kartanegara Regency, East Kalimantan. This lake has an area of approximately 11,000 hectares. This study aims to determine the type of fish, to determine the total number of fish per station, and to determine the diversity, uniformity, and dominance in Melintang Lake. There were 10 types of fish found. Rempang fish (Osteochilus repang) was the most common fish with 66 individuals. The highest composition was found at station 2. Diversity index at 3 stations ranged from 1.95-2.23. Uniformity ranged from 0.85-0.97 fish were evenly distributed. Dominance ranged from 0.11-0.18 which means that no dominant species was found